Longitudinal analysis of life values of adolescents with mental retardation and normotypical peers - Marina A. Vorobyova; Valentina V. Kolmakova; Anzhela V. Sokolova (Развитие образования)
The article presents the results of a longitudinal study comparing the dynamics of life values development in adolescents with mental retardation and normotypic peers. The study of the dominant values of normal adolescents and adolescents with mental retardation was carried out at the municipal autonomous educational institution secondary comprehensive school No. 157, Yekaterinburg, in the period from 2021 to 2023. The life values of adolescents were diagnosed using two methods: "Methodology for the Study of Value Orientations" (M. Rokeach), "Hierarchy of Life Values" (G.V. Rezapkina). The study showed that adolescents with mental retardation and normotypic peers have similar life values, but with some noticeable differences. These differences emphasize the importance of providing individual support to adolescents with mental retardation, which will contribute to their personal growth. The obtained data will also be of interest to teachers, parents and specialists who organize and implement correctional and developmental work, ensuring the well-being of adolescents with mental retardation. The study of the dynamics of the development of values of adolescents of the norm and mental retardation allowed us to conduct a comparative analysis and determine the trends in the formation of values in these categories of adolescents.